A Note on the Flare Stars in the Coalsack - Hidajat, B.; Kuncoro, A. (Journal of Mathematical and Fundamental Sciences, 2019)
Ringkasan. Didalam tulisan ini dilaporkan penemuan 5 buah "flare stars" di daerah Coalsack. Abstract. The discovery of 5 flare stars in the Coalsack is reported.